Dynamic parameters bobinopilar with three conical packaging bobinazhno – rewinding machines BP-340 - Oborski, Iwan; Akimov , Aleksandr; Lipinski, Tomasz (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
The results of the study of influence of inertia and stiffness parameters bobbin three conical packaging of critical speed. The mathematical model allows for elasticity supports bobbin with three conical packaging and fastening ukochuyuchoho roller. The resulting dependence of dynamic component of prytyskuvannya ukochuyuchoho roller to bobinopilar. The requirements for the fixation mechanism bobinotrymacha specifications. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)